ANALISIS PEMBERIAN KREDIT KONSUMTIF PADA PT. BANK SULAWESI TENGGARA CABANG UTAMA KOTA KENDARI - Aldin, Aldin; Utha, Arifin; Purwati, Ninik Endang (Universitas Halu Oleo, 2020)
This study aims to analyze the provision of consumer credit at PT. Bank Sultra, the main branch of Kendari. The informants in this study were employees of Bank Sultra who were actively involved in providing credit analysis. This type of research used in this research is to use a qualitative approach. Data collection uses: observation, interview, and documentation.The results showed that the procedure for granting and disbursing credit at PT. Bank of Southeast Sulawesi's main branch of Kendari must be in accordance with the provisions that have become the main requirements in the Bank of Southeast Sulawesi which includes stages: credit application, taking and filling out forms, completing all the requirements, the existence of a creditworthiness test, and credit approval as well as submitting documents that has been authorized to the bookkeeping section, and making proof of general expenditure by the cashier, the document is returned to the bookkeeping section, handing over money to the debtor, credit disbursement is recorded in the cash outlay recapitulation book by the cashier. ABSTRAK Penelitian ini bertujuan untuk menganalisis pemberian kredit konsumtif pada PT. Bank Sultra cabang utama Kendari. Adapun informan dalam penelitian ini adalah karyawan Bank Sultra yang sedang aktif terkait dengan analisis pemberian kredit. Jenis penelitian yang digunakan dalam penuliisan ini adalah dengan menggunakan pendekatan kualitatif. Pengumpulan data menggunakan: observasi, wawancara, dan dokumentasi.Hasil penelitian menunjukkan bahwa Prosedur pemberian dan pencairan kredit di PT. Bank Sulawesi Tenggara cabang utama Kendari harus sesuai dengan ketentuan yang sudah menjadi syarat utama pada Bank Sulawesi Tenggara yang mencakup tahapan: permohonan kredit, mengambil dan mengisi form, melengkapi segala hal yang menjadi persyaratan, adanya uji kelayakan kredit, dan persetujuan kredit serta penyerahan dokumen yang sudah diotorisasi ke bagian pembukuan, dan pembuatan bukti pengeluaran umum oleh kasir, dokumen dikembalikan ke bagian pembukuan, penyerahan uang kepada debitur, pengeluaran kredit dicatat pada buku rekapitulasi pengeluaran kas oleh kasir. Kata kunci : Pemberian kredit konsumtif PT. Bank Sultra Cabang Utama Kendari